New Methodologies in the Teaching of Hydraulics Based on Experimentation and CFD - Yoch, P.; Richard, P.; Jose, C. (International Association for Hydro-Environment Engineering and Research, 2019)
Lectures and experimental laboratories are fundamental elements for the teaching of hydraulics. The development and advance of this technology, gives us today the possibility of measuring, predicting and analyzing the behavior of a large number of hydraulic variables associated with an experiment; however, many of the hydraulics laboratories intended for teaching, do not have these facilities (e.g. PIV, LIST, ADV, Ultra-high-speed cameras, etc). In order to understand the behavior of flow patterns at different scales, this methodology has been implemented based on experimental data collection and complemented with sophisticated CFD Tools. The results of CFD models show mainly high spatial-temporal resolution hydraulic parameters, such as velocity profiles, water-air interface captures, turbulence, flow patterns, coherent turbulent structures, etc. This paper shows the results that we have obtained by complementing basic measurements of laboratory experiments with high-fidelity simulations with the use of HPC resources for five laboratory sessions and its implementation of the Open Channel Hydraulics course at Pontificia Universidad Católica del Perú.
Keywords: Hydraulics; Computational fluid dynamics; Computer science; Systems engineering; Engineering; Aerospace engineering; https://purl.org/pe-repo/ocde/ford#2.03.02